Implicancia del ácido hialurónico en la evasión de mecanismos de supresión tumoral, resistencia a multidrogas y activación de vías de señalización de líneas celulares leucémicas - Lompardía, Silvina Laura (2014)
The implication of hyaluronan (HA) in biological mechanisms involved in tumor progression was determined in this work. For this purpose the human leukemic cell lines K562 and Kv562 were used. We demonstrated that hyaluronan induced cell proliferation in both cell lines. On K562 cells the effect was mediated by CD44 trough activation of both PI3K/Akt and MEK/ERK pathways, whereas on Kv562 cells the effect was mediated by RHAMM and PI3K/Akt activation. The inhibition of HA synthesis by 4-methylumbelliferone (4MU) decreased both cell lines proliferation and sensitized Kv562 to the effect of Imatinib as well as VCR through Pgp and PI3K inhibition, in both cases with senescence induction. Moreover, hyaluronan oligomers (oHA) inhibited K562 proliferation mediated by CD44 as well as Akt and ERK down regulation. Furthermore, oHA sensitized Kv562 cells to both Imatinib and VCR by inhibition of Pgp as well as PI3K. We conclude that K562 and Kv562 cells synthesize HA to avoid senescence induction and resist chemotherapy. We postulate that HA synthesis would promote leukemia progression by triggering of the above-mentioned proliferative signals. These findings highlight the potential use of oHA and 4MU as coadjuvant for drug-resistant leukemia.